Human resource management and performance: A comparative study of Ireland and the Netherlands - Justine Horgan; Peter Mühlau (Management Revue, 2005)
In this article, we compare the effects of 'high performance human resource management' (HPHR) on employee and company performance between Ireland and the Netherlands. Key hypotheses are, first, that companies using the HPHR system exhibit higher levels of employee and company performance than companies that do not. Second, we expect that these relationships are stronger for Ireland than for the Netherlands as the societal context (skill formation, industrial relations and value systems) consistently support the working of HPHR in Ireland but in the Netherlands these institutions restrict the potential contribution of HPHR to performance improvements. These hypotheses are tested on company-level data from Ireland and the Netherlands. The main finding is that HPHR is associated with higher performance levels in Ireland but not in the Netherlands. Comparing the effects of single HR domains between the two countries further supports the institutional context hypothesis
Keywords: 650; human resource management; performance; societal effect; Ireland; the Netherlands; Personalmanagement; Unternehmenserfolg; Betriebsklima; Vergleich; Irland; Niederlande